RETRACTED: Comparative analysis of languages and frameworks for web application development - Degtyareva Ksenia; Evsyukov Dmitry; Boyko Andrei; Kukartseva Svetlana; Poddubnyy Andrey (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001